Soil health – a perspective - Fausak, Lewis K.; Bridson, Noa; Diaz-Osorio, Fernanda; Jassal, Rachhpal S.; Lavkulich, Les M. (Frontiers in Soil Science, 2024)
Governments and organizations are expressing growing concerns about soil health, driven largely by uncertainties of food security with an increasing human population and unpredictable effects of climate change. Although considerable literature and debate exist, there is discord around the question, what is a healthy soil? This is not surprising, given the complex roles the soil provides, from the range of food, fiber and medical products, hosting a biodiverse community, and supporting the water and nutrient cycles. While a consensus seems to suggest that a soil in good health should be able to provide goods and services in perpetuity, this does not define soil health, rather its provisioning functions. To explore the question, 'what is healthy?', we propose an analogy comparing indicators of human and soil health. For example, to identify the cause of a symptom, we compare the diagnostic pH in both humans and soil. Demonstrating the similarities between the way human and soil health concerns are addressed. Additionally, we consider the context that necessitates health and use a set of holistic predictors to link human and soil health further. In humans, genetics express many traits and can predispose one to certain illnesses or diseases, in the same way, parent material, soil texture, and length of time exposed to weathering can inform a soil's capability and predisposition for certain habitats or uses. In both cases, science informs the state of health and appropriate management solutions. We posit the null hypothesis "the concept of human health cannot be applied to soil".